The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6cc04323b
|View full text |Cite
|
Sign up to set email alerts
|

The organocatalytic ring-opening polymerization of N-tosyl aziridines by an N-heterocyclic carbene

Abstract: The ring-opening polymerization of N-tosyl aziridines, in the presence of 1,3-bis(isopropyl)-4,5(dimethyl)imidazol-2-ylidene as an organocatalyst and an N-tosyl secondary amine as initiator mimicking the growing chain, provides the first metal-free route to well defined poly(aziridine)s (PAz) and related PAz-based block copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 29 publications
(11 reference statements)
1
34
0
Order By: Relevance
“…This indicates a lower solvation of the living chain ends in THF, reducing the polymerization kinetics Table 5 Overview of the performed anionic polymerizations of 2-methyl-N-mesyl-aziridine with different gegenions and amounts of hexamethyldisilazane (at least by a factor of 10). In contrast, the conventional oxyanionic polymerization and the recently reported organocatalytic ring-opening polymerization of sulfonyl-aziridines 16 proceed smoothly in THF and reach full conversion in the course of several hours.…”
Section: Influence Of Counter-ionsmentioning
confidence: 83%
See 1 more Smart Citation
“…This indicates a lower solvation of the living chain ends in THF, reducing the polymerization kinetics Table 5 Overview of the performed anionic polymerizations of 2-methyl-N-mesyl-aziridine with different gegenions and amounts of hexamethyldisilazane (at least by a factor of 10). In contrast, the conventional oxyanionic polymerization and the recently reported organocatalytic ring-opening polymerization of sulfonyl-aziridines 16 proceed smoothly in THF and reach full conversion in the course of several hours.…”
Section: Influence Of Counter-ionsmentioning
confidence: 83%
“…4,9 We have developed new monomers and initiator-systems during the last few years, expanding this still rather unexplored approach to polysulfonamides and amines. [5][6][7][8]15,16 With a similar ring-strain of 111 kJ mol −1 for ethylene imine as for ethylene oxide (114 kJ mol −1 ), the anionic ringopening polymerization should be feasible. 17,18 In contrast to unsubstituted ethylene imine, which can only be polymerized via a cationic mechanism, leading to branched PEI ( poly(ethylene imine)), 19 N-protected aziridines can also be polymerized anionically, due to their activating group.…”
Section: Introductionmentioning
confidence: 99%
“…First, the variation of the alkyl chain at the 2‐position of the aziridine ring allows to attach functional or solubilizing groups. We demonstrated that steric groups such as C‐10 chains or bulky phenyl groups do not hamper the polymerization . In addition, the electron withdrawing group, which is attached to the aziridine ring by a cleavable sulfonamide, can be used as a handle to control chemical function .…”
Section: Resultsmentioning
confidence: 98%
“…We demonstrated that steric groups such as C-10 chains or bulky phenyl groups do not hamper the polymerization. [22,25] In addition, the electron withdrawing group, which is attached to the aziridine ring by a cleavable sulfonamide, can be used as a handle to control chemical function. [18,26] The electron withdrawing behavior activates the aziridine and thereby influences the polymerization kinetics.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…The first living OROP of 2-alkyl-N-sulfonyl aziridines was presented by Carlotti, Taton and coworkers in 2016 (Scheme 21). 147 The OROP of N-tosyl-2-substituedaziridines takes place in the presence of 1,3-bis(isopropyl)-4,5 (dimethyl)imidazole-2-ylidene, as a sterically hindered organocatalyst, and activated secondary N-tosyl amine as the initiator. This mechanism offers a mild and metal-free route for the polymerization of activated aziridines to obtain identical poly-aziridines to those from AROP, with narrow molecular weight distributions (1.04 < Đ < 1.15) and molecular weights up to 21 000 g mol −1 .…”
Section: Organocatalytic Ring-opening Polymerization (Orop) Of Activamentioning
confidence: 99%